Neuroaesthetics: exploring the role of aesthetic experience in neurorehabilitation - Colombi, Francesca; Varesio, Greta; Selini, Enrico; Amighetti, Elia; Crepaldi, Maura; Fusi, Giulia; Ronga, Irene; Cancer, Alice; Antonietti, Alessandro; Geminiani, Giuliano Carlo; Rusconi, Maria Luisa (Frontiers in Psychology, 2025)
The rise in life expectancy, along with other factors, leads to an increase in neurodegenerative diseases and stroke. Research in neuropsychological fields is working toward developing innovative methods to address and treat the cognitive disorders that can result from these conditions, such as non-pharmacological interventions (e.g., cognitive stimulation training). As an emerging field, neuroaesthetics explores the cognitive processes and neural foundations associated with aesthetic experiences. As demonstrated by the “Michelangelo Effect,” observing artworks stimulates brain regions and emotional responses that could positively impact the effectiveness of neurorehabilitation protocols. This article aims to present an overview of existing theories and models that provide a framework for understanding the possible role of aesthetic appreciation in neurological and cognitive rehabilitation.